Electric field-induced alignment of nanofibrillated cellulose in thermoplastic polyurethane matrix. (1st March 2018) - Xu, Shuman; Liu, Dingyao; Zhang, Qin; Fu, Qiang
Abstract: Nanofibrillated fibers (NFC) has been largely used as reinforcing filler to improve the properties of polymer matrix because of their unique properties such as high aspect ratio, good aqueous stability, high specific strength and stiffness. However, the full potential of NFC as reinforcing agent has not been realized because of its poor dispersion and random distribution in polymer matrix. In this work, we demonstrate the importance of alignment of NFC to determine the mechanical properties of polymer via applying alternative current (AC) electric field and using thermoplastic polyurethane (TPU) as the matrix. The TPU/NFC nanocomposites were prepared via solution casting method and the effect of parameters of the applied electric field (amplitude, frequency as well as the duration of application) on the orientation degree of NFC and the final properties of TPU/NFC nanocomposites are systematically investigated. It was found that NFC could be easily oriented under effect of AC due to electric induced polarization. The prepared anisotropic TPU/NFC composites exhibit 2.07 and 1.82 times increase of tensile strength and elongation at break in the parallel direction than that in the vertical direction for the anisotropic samples, respectively. It was also interesting, to find that the samples with aligned NFC exhibit an increased dielectric constant with lower dielectric loss, which could provide an idea to fabricate high performance dielectric materials.